Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Beyond Perceived Discrimination: Weight Discrimination in College Social Networks Is Associated With Poorer Mental and Behavioral Health - Alena C. Borgatti; Andrea L. Davis; Gareth R. Dutton (Journal of the Academy of Nutrition and Dietetics, 2025)

Body fat and circulating leptin levels in the captive short-beaked echidna (Tachyglossus aculeatus) - Kate J. Dutton-Regester; Alice Roser; Haley Meer; Andrew Hill; Michael Pyne; Aiman Al-Najjar; Tim Whaites; Jane C. Fenelon; Katherine L. Buchanan; Tamara Keeley; Marilyn B. Renfree; Stephen D. Johnston (Journal of Comparative Physiology B, 2024)
It is possible that the reproductive strategy of the short-beaked echidna is related to seasonal changes in fat deposition and energy availability, regulated by seasonal changes in endocrine function. We predicted that circulating leptin levels would be directly proportional to adiposity during most of the year, but that a change in this relationship would occur during the pre-breeding season to allow increased fat deposition. To test this hypothesis, we made use of a captive colony of echidnas to describe and quantify changes in fat distribution and the adipostatic hormone leptin. First we assessed seasonal changes in circulating leptin levels, body mass and adiposity for three male and three female adult echidnas maintained on a standard diet. Second, we explored the relationship between circulating leptin levels and increased caloric intake for an additional five adult female echidnas that were provided with supplemented nutrition. Third we visualised fat distribution in male and female adult echidnas using magnetic resonance imaging (MRI) before and after the breeding season, to determine where fat is deposited in this species. For echidnas maintained on the standard diet, there were no seasonal changes in body mass, body fat or plasma leptin levels. However, female echidnas provided with supplemented nutrition had significantly elevated plasma leptin levels during the breeding season, compared to the pre-and post- breeding periods. MRI showed substantial subcutaneous fat depots extending dorso-laterally from the base of the skull to the base of the tail, in both sexes. Pre-breeding season, both sexes had considerable fat deposition in the pelvic/rump region, whilst the female echidna accumulated most fat in the abdominal region. This study shows that male and female echidnas accumulate body fat in the pelvic/rump and the abdominal regions, respectively and that circulating leptin may promote fattening in female echidnas during the breeding season by means of leptin resistance. However, further research is required to evaluate the precise relationship between seasonal changes in leptin and adiposity.

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fecal steroids as a potential tool for conservation paleobiology in East Africa - Andrew C. Kemp; Christopher H. Vane; Alexander W. Kim; Christopher L. Dutton; Amanda L. Subalusky; Stuart K. Kemp; Andrew C. Parnell (Biodiversity and Conservation, 2022)

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

Novel “filter pellet” sample preparation strategy for quantitative LA-ICP-MS analysis of filter-bound sediments: a “green chemistry” alternative to sediment fingerprinting in Tanzania’s Ruvu River basin - Sarah C. Jantzi; Christopher L. Dutton; Amartya Saha; Rosemary Masikini; Jose R. Almirall (Journal of Soils and Sediments, 2019)

Genetic fingerprinting reveals natal origins of male leatherback turtles encountered in the Atlantic Ocean and Mediterranean Sea - Suzanne E. Roden; Kelly R. Stewart; Michael C. James; Kara L. Dodge; Florence Dell’Amico; Peter H. Dutton (Marine Biology, 2017)

Diseases of captive yellow seahorse Hippocampus kuda B leeker, pot‐bellied seahorse Hippocampus abdominalis L esson and weedy seadragon Phyllopteryx taeniolatus ( L acépède) - V LePage; J Young; C J Dutton; G Crawshaw; J A Paré; M Kummrow; D J McLelland; P Huber; K Young; S Russell; L Al‐Hussinee; J S Lumsden (Journal of Fish Diseases, 2015)
Seahorses, pipefish and seadragons are fish of the F amily S yngnathidae. From 1998 to 2010, 172 syngnathid cases from the T oronto Z oo were submitted for post‐mortem diagnostics and retrospectively examined. Among the submitted species were yellow seahorses Hippocampus kuda Bleeker ( n = 133), pot‐bellied seahorses Hippocampus abdominalis Lesson ( n = 35) and weedy seadragons Phyllopteryx taeniolatus ( L acépède; n = 4). The three most common causes of morbidity and mortality in this population were bacterial dermatitis, bilaterally symmetrical myopathy and mycobacteriosis, accounting for 24%, 17% and 15% of cases, respectively. Inflammatory processes were the most common diagnoses, present in 117 cases. Seven neoplasms were diagnosed, environmental aetiologies were identified in 46 cases, and two congenital defects were identified.

Biological electron tunneling through native protein media - C. C. Moser; C. C. Page; X. Chen; P. L. Dutton (JBIC Journal of Biological Inorganic Chemistry, 1997)